BACKWARD PRODUCTION OF A SPIN PARITY 1+RHOPI ENHANCEMENT AT 1.04 GEV - Gavillet, P; Berge, P; Ferrando, A; Hemingway, R; Holmgren, S; Losty, M; Marin, J; Montanet, L; Pagiola, E; Yamdagni, N; Blokzijl, R; Jongejans, B; et al. (1977)
A spin-parity 1+ρ{variant}π enhancement is observed for the 3π mass spectrum in the reaction K-p → Σ-π+π+π- where events with a small (K- → Σ-) momentum transfer are selected. The mass (1040 MeV) and width (230 MeV) of this enhancement are reminiscent of the A1 → ρ{variant}π bump which has mainly been observed in the diffractive-like processes. The cross section for this enhancement at 4.15 GeV/c incident K- momentum is (3.6 ± 0.5) μb. © 1977.